"What matters to you?" A longitudinal qualitative study of Norwegian patients' perspectives on their pathways with colorectal cancer. Issue 1 (1st January 2018) - Hansen, Frank; Berntsen, Gro K. Rosvold; Salamonsen, Anita
ABSTRACT: Purpose : Person-centred care (PCC) is a well-acknowledged goal throughout the western world both within the health care services sector and for the patients themselves. To be able to create a future health care system that includes improved PCC, we need more in-depth knowledge of what matters to patients, how "what matters" might change over time, and tentative descriptions of commonalities across patients' perspectives. The aim of this study is to contribute to this knowledge base. Methods : We conducted a qualitative interview series over one year with nine Norwegian patients who were recently diagnosed with rectal cancer tumor-node-metastasis stage I–III. Results : We found that: (1) patients have an initial focus on "biological goals" and conventional treatment; (2) pathways are unique and dynamic; (3) family and friends affected patient pathways positively with respect to meaningfulness and quality of life, but for some participants also negatively because there were heavy burdens of caretaking; (4) receiving help in the health care system depended on the patients' navigation skills; (5) pluralism in health-seeking behaviour was important in all patient pathways. Conclusion : Long lasting illness may be a dynamic and complex journey. These results represent some features of a pathway with cancer and are important because they contribute with knowledge about what matters most seen from the cancer patients' point of view.